Design and validation of the Sport Psychology FAN digital learning application for sports psychology courses - Fitri Agung Nanda; Silvi Aryanti; Soleh Solahuddin; Alvin Anggara (Sriwijaya Journal of Sport, 2026)
Research Problems: Despite the increasing use of digital learning media in higher education, validated digital applications specifically designed for sports psychology courses remain limited. Therefore, rigorous validation is needed to ensure their content accuracy, instructional quality, and technical functionality before classroom implementation. Research Objectives: This study aimed to evaluate the content, media, and technical validity of a digital learning application for sports psychology courses entitled Sport Psychology Is FAN. Methods: The study employed a Level 1 Research and Development (R&D) approach, focusing on product design and expert validation before field implementation. A total of 21 specialists in educational technology and sports psychology participated in the validation process. Data were collected using structured validation instruments covering three aspects: learning media, content, and application quality. The validity of the application was analyzed using Aiken’s V coefficient. Results: The results demonstrated a high level of validity across all evaluation aspects, with Aiken’s V values of 0.857 for learning media, 0.892 for content, and 0.821 for application quality. These findings indicate that the application possesses strong content accuracy, instructional media quality, and technical functionality, meeting the criteria for educational use. Although several suggestions for improvement were identified, the overall evaluation confirmed that the application is suitable for supporting learning in sports psychology courses. Conclusion: This study provides empirical evidence for the validity of the "Sport Psychology Is FAN" application and establishes a foundation for future research examining its effectiveness in enhancing student learning outcomes and engagement in higher education.